2020
DOI: 10.1177/0361198120949877
|View full text |Cite
|
Sign up to set email alerts
|

Intermodal Connection of High-Speed Rail with Interregional Bus Services in Japan

Abstract: An intermodal transportation service consisting of high-speed rail (HSR) and an interregional bus service is one policy option for rural areas where interregional travel demand is too low to justify the construction of HSR. This study reviews current interregional bus services connecting with interregional rail, particularly HSR, in Japan, and analyzes the market potential for improving intermodal transportation by integrating HSR with an interregional bus service. It reviews the current interregional transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Such poor connections can discourage potential passengers from using connected means of transportation, like a train plus a bus. Nevertheless, it is very problematic to implement all of the connections well, and there are many conflict requirements that make a perfect implementation for all connections impossible [47].…”
Section: Autonomous Vehicles Renounce the Need For Rail Systemsmentioning
confidence: 99%
“…Such poor connections can discourage potential passengers from using connected means of transportation, like a train plus a bus. Nevertheless, it is very problematic to implement all of the connections well, and there are many conflict requirements that make a perfect implementation for all connections impossible [47].…”
Section: Autonomous Vehicles Renounce the Need For Rail Systemsmentioning
confidence: 99%
“…A study in South Korea suggests that the probability of choosing an intercity coach is more sensitive to HSR invehicle time and HSR ticket price than the probability of choosing cars (Lee et al, 2004). Based on surveys conducted by the Ministry of Land, Infrastructure, Transport and Tourism of Japan, Yashiro and Kato (2020) found that an improvement in the intermodal connection between HSR and interregional buses that mainly connect to cities without HSR stations can also effectively shift car and conventional rail users to rail-bus intermodal services.…”
Section: Hsr-roadmentioning
confidence: 99%
“…It has been deter-mined that airport development is all about "connectivity and growth" [5]. Especially, in this year, people have experienced a strong and durable channel of airport collaborations throughout the world and there must be a complete constructive viewpoint for the "global aviation industry" [6]. The major role that has been played in this industry is by the reasonable oil rates and recovery of the economic factor, which is still constructing (although gradually).…”
Section: Need For Regional Development Of Airports In Japanmentioning
confidence: 99%